Deciphering Cadmium (Cd) Tolerance in Newly Isolated Bacterial Strain, Ochrobactrum intermedium BB12, and Its Role in Alleviation of Cd Stress in Spinach Plant (Spinacia oleracea L.) - Renu, S.; Sarim, Khan Mohd.; Singh, Dhananjaya Pratap; Sahu, Upasana; Bhoyar, Manish S.; Sahu, Asha; Kaur, Baljeet; Gupta, Amrita; Mandal, Asit; Thakur, Jyoti Kumar; Manna, Madhab C.; Saxena, Anil Kumar (Frontiers in Microbiology, 2022)
A Cadmium (Cd) tolerant bacterium Ochrobactrum intermedium BB12, was isolated from sewage waste collected from municipal sewage dumping site of Bhopal, India, which possess multiple heavy metal tolerance and had maximum minimum inhibitory concentration of 150 mgL-1 of Cd. Growth kinetics, biosorption, Scanning Electron Microscopy (SEM), Transmission electron microscopy (TEM) and Fourier Transform Infra-Red spectroscopy (FTIR) studies on BB12 in presence of Cd suggested biosorption as primary mode of interaction with Cd. SEM and TEM studies revealed surface deposition of Cd, and FTIR spectra indicted nitrogen atom in exopolysachcarides secreted by BB12 to be the main site for Cd attachment. The potential of BB12 to alleviate the effect of Cd stress at 25, 50 and 75 mgkg 1 soil on Spinach (Spinacia oleracea L.) var. F1-MULAYAM was also evaluated. Without bacterial inoculation, plant showed delayed germination, decrease in chlorophyll content and stunted growth at 50 and 75 mgkg 1 Cd. Bacterial inoculation resulted in early germination, increased chlorophyll and 28.33% and 72.60% increase in shoot and root fresh weight, respectively, at 50 mgkg 1 of Cd stress after 75 days of sowing. Elevated proline accumulation and superoxide dismutase enzyme production in Cd stressed plants was lowered down on bacterial inoculation. The strain is capable of biosorbing Cd from the soil as evident from significant reduction in uptake/translocation and bioaccumulation of Cd in bacteria treated spinach plants. The application of O. intermedium BB12 can be a promising approach to reduce to Cd toxicity in crops grown in Cd contaminated soil.